Pengaruh Efektivitas Penerapan Cost Dan Expense Terhadap Tingkat Revenue Pada Hotel Mercure Jakarta Sabang (2019-2022) - Calpin Harris Miantua Marbun; Eka Budi Yulianti; Desyi Erawati (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to examine the effect of affectiviness the application of cost and expense emphasis on revenue levels at the Mercure Jakarta Sabang Hotel (2019-2022). The type of data used is qualitative data. The research method used is quantitative research. The data analysis technique used multiple regression analysis which was preceded by normality, multicollinearity, and heteroscedasticity tests. From the calculation results that partially there is a significant effect of cost on revenue. Expenses have a significant effect on revenue. The results simultaneously show that costs and expenses have a significant effect on revenue.